Cultural discourses in Ceauşist Romania: the hero-mirror mechanism - Boicu, Filip Sebastian (2014)
This thesis is concerned with main cultural discourses of the second phase of Communism in Romania (1964-1989), period largely identical with that of Ceauşescu’s rule. A secondary aim of the thesis is to look at the post-1989 continuations of these publicly influential discourses with the aim of understanding how the educational system (HE, in particular) is positioned in relation to the cultural domain. With regard to the Communist period, the main assertion of the thesis is that analysis of these discourses reveals an underlying cultural mechanism equivalent with a central mode of governance employed by the Communist party. According to this assertion, the mission of this cultural mechanism, with origins in Lenin’s drastic distinction between the party and the proletariat and in the idea that the party must bestow consciousness on the proletariat, is to create and regulate positive avatars (heroes imbued with the best of humanity) for each social category so as to fulfill and safeguard the aims of the Party. For this reason, this device has been entitled the hero-mirror mechanism. The device has also been linked with religion and theology. This perspective has found that the mirror-mechanism corresponds to the notion of “imago Dei,” and its axes to the notions of “kenosis” and “imitatio Dei.” The assessment of these cultural discourses via the mirror-mechanism results in three dimensions of research, each with its own universes of investigation, and each with its own findings. In the first dimension, the mirror-mechanism deals with discourses as identity, and thus with the deconstruction of Romanian identity. If, as observed, the mirror-mechanism receives its first major blow in the 1980s and begins to crumble after 1989, what has replaced it since and with what implications for Romanian identity? The second dimension views the same discourses as mainly intellectual. Here, the notion of ‘inner utopia’ is highlighted as a dominant and recurring theme, and, therefore, as possibly the dominant feature of the Romanian cultural/political scene during and after Communism. If, because of the notion of ‘inner utopia,’ ‘true education’ is viewed as lying outside the provinces of formal institutions, what then is the educational role ascribed to the public space in relation to the HE system? Finally, the third dimension assesses these discourses in terms of their claims for anti-Communist resistance while providing a typology for elucidating such claims.